The Impact of Village-Owned Enterprise (BUMDes) Management on Village Economic Development in Botto Village Takkalalla District Wajo Regency - Aris, Muhammad (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
This study aims to determine the impact of the management of Village-Owned Enterprises (BUMDes) on the economic development of the village in Botto Village, Takkalalla District, Wajo Regency. The management of BUMDes is expected to enhance the village economy through efficient management in accordance with established standards. This research employs a quantitative method with a census approach, where all BUMDes managers in Botto Village are used as samples. The research findings indicate that the management of BUMDes in Botto Village is categorized as very good and has a positive impact on the economic development of the village. This is evident from the dimensions of BUMDes management, which include cooperative, participatory, emancipatory, transparent, accountable, and sustainable, all of which are classified as good. Similarly, the village's economic development, which includes agricultural sector growth, national integration, and economic justice, is categorized as very good. This study provides an overview that good BUMDes management can improve village economy through various existing potential sectors.